m=(m+1)+(2m-1)

Simple and best practice solution for m=(m+1)+(2m-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m=(m+1)+(2m-1) equation:


Simplifying
m = (m + 1) + (2m + -1)

Reorder the terms:
m = (1 + m) + (2m + -1)

Remove parenthesis around (1 + m)
m = 1 + m + (2m + -1)

Reorder the terms:
m = 1 + m + (-1 + 2m)

Remove parenthesis around (-1 + 2m)
m = 1 + m + -1 + 2m

Reorder the terms:
m = 1 + -1 + m + 2m

Combine like terms: 1 + -1 = 0
m = 0 + m + 2m
m = m + 2m

Combine like terms: m + 2m = 3m
m = 3m

Solving
m = 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
m + -3m = 3m + -3m

Combine like terms: m + -3m = -2m
-2m = 3m + -3m

Combine like terms: 3m + -3m = 0
-2m = 0

Divide each side by '-2'.
m = 0

Simplifying
m = 0

See similar equations:

| 2c^2-10c-168= | | [30-7x]=4 | | 9y=163 | | X+14-8x=7 | | 8x+4=120 | | 3X+24/7+X+14/4=11 | | 3x+1=p | | abs(5x)/x | | 3(5+2x)=9 | | 2y-1=3y+2 | | d-6r=-r | | x/175=45/100 | | [8x+1]=23 | | 3+5x+7=2(4+1)+10x | | (3/4x^3y^2)^2 | | 5-x=8x-13 | | 7(3n+4)=7(6n+4)+9 | | 17k-9=3k-8k | | 0.04x+0.03(s+200)=27 | | [2n-5]=7 | | 14.50p=53 | | 2s-4=2s | | 5+3x-7=4x-2-x | | (1/5q)=9-(2/5q) | | 2x=p | | 4y-3+y+34=7y+40-5y | | 3x+15/6+x+23/4=15 | | [22-3n]=5 | | 5E^2+6E=6E^3 | | 180=x+5x+(x+5) | | 1/3(6-15w)=3/8(40w-8)+10 | | x/175=45% |

Equations solver categories